2008
DOI: 10.2341/07-151
|View full text |Cite
|
Sign up to set email alerts
|

Repairing Ceramic Restorations: Final Solution or Alternative Procedure?

Abstract: PURPOSEThis article provides an overview of dental ceramics. It addresses possible modes of failure and factors that may influence the decision to either repair or replace ceramic restorations. The authors' intention was to present ceramic repair as a reliable, low-cost, low-risk technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 16 publications
2
52
0
1
Order By: Relevance
“…Intra-oral repair of cohesively fractured ceramic crowns with resin composite can be considered a cost and time effective method with the advantage of maintaining the restoration substructure and therefore protecting the underlying tooth 54,55) . The alternative is to replace the crown, removal of which is a difficult process, and producing an aesthetic replacement.…”
Section: Discussionmentioning
confidence: 99%
“…Intra-oral repair of cohesively fractured ceramic crowns with resin composite can be considered a cost and time effective method with the advantage of maintaining the restoration substructure and therefore protecting the underlying tooth 54,55) . The alternative is to replace the crown, removal of which is a difficult process, and producing an aesthetic replacement.…”
Section: Discussionmentioning
confidence: 99%
“…To date, documentation on the clinical performance of repaired restorations is sparse and scanty 10) . Different repair protocols have been developed, and evaluated by researchers, to enhance the functionality, longevity, and esthetics of ceramic restorations: acid etching (e.g., hydrofluoric acid, acidulated phosphate fluoride, and phosphoric acid) 2,[11][12][13][14] , airborne particle abrasion with aluminum oxide 15) , and airborne particle abrasion with silica coating [16][17][18] . However, there is no agreement on which repair system is the efficient one that guarantees favorable clinical outcome 16) .…”
Section: Introductionmentioning
confidence: 99%
“…The repair is characterized by a faster and low-cost method if compared to replacement of the entire restoration (3)(4)(5). This study has shown that using the correct surface treatment for each ceramic is the key for success in repair procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The feldspathic ceramics used as veneer are commonly affected by shipping, fracture or excessive wear, mainly when supported by zirconia frameworks (2). In this way, direct repair with a composite resin appears as an attractive alternative due to the low cost, fast resolution, and preservation of supporting structures (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%